ANALISIS KESALAHAN PESERTA DIDIK KELAS X DALAM MENYELESAIKAN SOAL MATEMATIKA MENURUT TAHAPAN KASTOLAN PADA MATERI NILAI MUTLAK - Ihsanul Fajri (Jurnal Edukasi dan Penelitian Matematika, 2022)
This study goals to analyze and describe the kinds of errors made by students in completing absolute values based on the Kastolan stages and to discover what influenced students to make errors in solving issues. This type of studies is descriptive qualitative with studies subjects are 9 students of class X MIPA 1 SMA Sumpah Pemuda. The data collection technique was in the form of a written test which was arranged in essay exam as many as 10 questions, interviews, distributing questionnaires and studying documentation. The analysis technique used in this study is data reduction, data presentation and conclusion drawing. From the results of student rethe analysis of student errors, the most errors made by students were conceptual errors namely 56.04%, then technical errors by 33.62% and strategy errors by 10.34%. Many factors that cause students can be wrong in answering math questions on absolute value material are caused by internal factors generally in low physical conditions such as lack of concentration during the learning process, there are still many students who still don't like learning mathematics which can result in lower students math scores than any other lesson. Keywords – Types of  Kastolan Errors, Absolute Value, Factors Causing Errors